Emperor and Ancestor : State and Lineage in South China. - Faure, David (Stanford University Press, 2007)
Faure argues that, in China, ritual provided the social glue which law provided in the West. He traces the special lineage institutions for which south China has been noted and argues that they fostered the mechanisms which enabled south China to be absorbed into the imperial Chinese state - first, by introducing rituals that were acceptable to the state, and second, by providing mechanisms which made group ownership of property feasible and hence possible to pool capital for land-reclamation projects important to the state.